Plan de nacimiento: Una mirada de los profesionales de la salud en portugal - Pinheiro, Arminda; Sardo, Dolores (Ediciones ROL, 2020)
Introduction: The birth plan (BP) is a written document prepared by the couple to express their wishes regarding birth. It has been the subject of health studies, although in Portugal there is a lack of research. Objective: To identify the perception of health professionals (HP) about the BP in Portugal. Methods: qualitative, exploratory, descriptive study with self-completed questionnaire on an online platform. Anonymity and confidentiality guaranteed. We used the content analysis according to Bardin and the INVivo12 tool. The non-probabilistic, intentional sample with 44 nurses midwives. Results and discussion: The BP was associated with the descriptors: empowerment and decision, humanization, choice and respect. 72.7% informed the woman/couple during the prenatal appointment and in childbirth classes. 47.7% assisted in its construction; 50% reported difficulties due to lack of model, non-acceptance and fears of HP reactions. 93.1% thought that their presentation to the team is important; 63.6% considered that BP isn’t respected in maternities for institutional and professional reasons; 90.9% considered that the HP reacts in several ways to the presentation of the BP, from the devaluation to the need for its institutionalization. The results show that, although we are in different stages of BP implementation, the difficulties presented are similar to those developed in Europe. Conclusions: The results show that the HP recognize the advantages of the BP as a facilitating and reorientation strategy for women/couples in childbirth, promoting respectful and citizen-centered care. From conception to implementation, the BP seems to be a still incipient practice in Portugal. The HP considers necessary to create policies for the implementation and development of BP, important for citizens as well as for the HP.
Birth plan: a look of the health professionals in Portugal
Keywords: Health professionals; Birth plan